Nanocellulose-based carbon nanocomposite for the electrochemical sensing application for pharmaceuticals: A review - Shalauddin, Md; Basirun, Wan Jeffrey; Shamima, Akhter; Hashem, Abu; Ab Rahman , Marlinda (Malaysian NANO-An International Journal, 2023)
Biopolymers are naturally occurring polymers which have attained profound interest and are investigated widely due to their outstanding characteristics and several advantages such as cost efficiency, hydrophilicity, film formation capability, chemical inertness, non-toxicity, high mechanical integrity and biocompatibility. Cellulose is the most abundant biopolymer in the world. Nanocellulose (NC) is a cost-efficient, biodegradable, eco-friendly, biocompatible and abundant, renewable biomaterial obtained from cellulose by nanoscale isolation. The most interesting property of NC as the precursor material, is that it does not possess hierarchical structural defect. Recently, the incorporation of NC into electroconductive platforms i.e., nanostructured carbon nanocomposite is a hot topic for researchers. NC is not an electroconductive material but an ionic conductor. Availing this property NC can be incorporated with carbon-based materials. CNTs is a carbon-based material with excellent electronic properties, high electroconductive and mechanical properties. This review focuses on the application of nanocomposites containing NC and carbon nanostructured especially CNTs and their properties and sensing applications.